The Effect of Perceived Organizational Support and Leader-Member Exchange on Organizational Commitment in Muhammadiyah Waqf Organization - Umam, Moh Rifqi Khairul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Muhammadiyah, as one of the oldest Islamic organizations in Indonesia, is an organization that has been active in the management of waqf for a long time, which has a tremendous social impact on Indonesian society. However, this organization is still facing obstacles in the direction of reliable human resources for waqf managers. Organizational commitment is a vital aspect in shaping this superior human resource, and social exchange theory has long been recognized as a critical factor in explaining the formation of this organizational commitment. By focusing on perceived organizational support (POS) and leader-member exchange (LMX) factors, this study offers research results in the form of proven influence of POS on organizational commitment, the absence of LMX influence on organizational commitment, POS influence on LMX, and no evidence of LMX impact as a mediating variable on the effect of POS on organizational commitment.